LIBRARY AUTOMATION SOFTWARE IN MAHARASHTRA: AN OVERVIEW - Mr. Datta Sopanrao Solanke (International Journal of Multidisciplinary Research and Studies, 2023)
Books are a knowledge treasure for students, youths, etc. They contribute to transforming the youths into civilized citizens. In this regard, libraries play a significant role in shaping the generations. Technology has a significant impact on improving reach, accessibility, digitalization, automation, book management, online databases, publications, etc. Library automation helps libraries and library patrons use library resources effectively. It is streamlined because of computers and software. Automation is a process of using machinery for easily work and saving human power and time. The main purpose of library automation is to free the librarians and library staff and to allow them to contribute more meaningfully to the spread of knowledge and Information. In the said article, information about the library software used in the libraries of Maharashtra state has been given.